Retrieval analysis of alumina ceramic-on-ceramic bearing couples. (April 2014) - Korim, Muhammad; Scholes, Susan; Unsworth, Anthony; Power, Richard
<x xml:space="preserve">Abstract</x> Background and purpose — Ceramic-on-ceramic (CoC) bearings have been in use in total hip replacement (THR) for more than 40 years, with excellent long-term survivorship. Although there have been several simulator studies describing the performance of these joints, there have only been a few retrieval analyses. The aim of this study was to investigate the wear patterns, the surface properties, and friction and lubrication regimes of explanted first-generation alumina bearings. Materials and methods — We studied 9 explanted CoC bearings from Autophor THRs that were revised for aseptic loosening after a mean of 16 (range 7–19) years. The 3D surface roughness profiles of the femoral heads and acetabular cups (Srms, Sa, and Ssk) were measured to determine the microscopic wear. The bearings were imaged using an atomic-force microscope in contact mode, to produce a topographical map of the surfaces of the femoral heads. Friction tests were performed on the bearing couples to determine the lubrication regime under which they were operating during the walking cycle. The diametral clearances were also measured. Results — 3 femoral heads showed stripe wear and the remaining 6 bearings showed minimal wear. The femoral heads with stripe wear had significantly higher surface roughness than the minimally worn bearings (0.645 vs. 0.289, p = 0.04). High diametral clearances, higher than expected friction, and mixed/boundary lubrication regimes prevailed in these retrieved bearings. Interpretation — Despite the less than ideal tribological factors, these first-generation CoC bearings still showed minimal wear in the long term compared to previous retrieval analyses.